Analisis Penentuan Keuntungan Berdasarkan Etika Bisnis Di Indonesia - Anjel Ezania Sihombing; Ajeng Windi Astuti; Lutfiah Nur Azizah; Bonaraja Purba (Public Service and Governance Journal, 2024)
Business ethics can be defined as knowledge about the ideal procedures for regulating and managing a business that takes into account norms and morality that apply universally and economically/socially, and the application of these norms and morality supports the aims and objectives of business activities. Determining profits based on business ethics is not always easy, so companies must pay attention to the fact that implementing business ethics is very important, because this can provide long-term benefits for the company and society as a whole. This research aims to find out how to determine profits based on business ethics in Indonesia. The method used in this research is a descriptive research method using a qualitative approach. The research results show that good business activities strive to achieve profits by paying attention to corporate social responsibility (CSR) and the application of business ethics in determining profits involves a balance between achieving financial goals and paying attention to social, environmental and moral impacts.